2011
DOI: 10.1099/jmm.0.028001-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in Kuwaiti children: association of clinical characteristics with Cryptosporidium species and subtypes

Abstract: To determine the association of clinical characteristics with Cryptosporidium types and subtypes, faecal specimens from 2548 children with diarrhoea were screened by microscopy for Cryptosporidium spp., and positive specimens were genotyped and subtyped by PCR-RFLP. A total of 87 of the 2548 children (3.4 %) had cryptosporidial diarrhoea by microscopy and the majority (41.4 %) of the infected children were in the 4-8-year-old age group. Molecular characterization of the 83 children studied further (4 had mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 31 publications
4
43
1
Order By: Relevance
“…However the C. parvum IIa subtype family usually described as zoonotic was reported previously as being associated to anthroponotic transmission in developing countries [9]. Similarly to the present study, iIqbal et al reported Ia and Ie C. hominis and IIa and IId C. parvum as the more frequent subtype families among children from Kuwait [54].…”
Section: Discussionsupporting
confidence: 87%
“…However the C. parvum IIa subtype family usually described as zoonotic was reported previously as being associated to anthroponotic transmission in developing countries [9]. Similarly to the present study, iIqbal et al reported Ia and Ie C. hominis and IIa and IId C. parvum as the more frequent subtype families among children from Kuwait [54].…”
Section: Discussionsupporting
confidence: 87%
“…In Saudi Arabia, the incidence of C. parvum was 42.9%, followed by 37% of C. hominis , C. meleagridis and C. muris in one sample (29). In Kuwait C. parvum and C. hominis were detected in 73% and 27% of isolates, respectively (30). …”
Section: Discussionmentioning
confidence: 99%
“…4,[11][12][13][14] According to WHO, diarrhea is regarded as the second highest cause of morbidity and mortality among the children in developing countries, 1 for which cryptosporidiosis and rotavirus are the most common parasitic and viral cause for gastroenteritis worldwide. 2 Comparing with studies carried out in other Iraqi provinces, our record was much lower than that reported by 11,12 in children aged less than three years old in Erbil and Sulaimani, respectively.…”
Section: Discussionmentioning
confidence: 99%